Exploring the Key Factors of Shared Decision-Making Through an Influential Network Relation Map: The Orthopedic Nurse's Perspective - Jin, Yanjun; Hong, Haiyan; Liu, Chao; Chien, Ching-Wen; Chuang, Yen-Ching; Tung, Tao-Hsin (Frontiers in Medicine, 2022)
Background. Few studies have used quantitative methods to explore the key factors affecting shared decision-making (SDM) in nursing decision-making from the perspective of orthopedic nurses. Purpose. To understand the intercorrelations among shared decision-making questionnaire–nurse (SDM-Q-NUR) factors and identify key factors for clinical nursing care decisions in orthopedics. Methods. In May 2021, this study investigated the interdependence of the SDM-Q-NUR scale and developed an influence network relation map (INRM) from the clinical experience of 13 trained orthopedic nurses using the Decision-making Trial and Evaluation Laboratory method. Results. The INRM results showed that the nine criteria corresponded to three stages: preparation, discussion, and decision. “I helped my patient or patient’s family understand all the information” ( ) and “I wanted to know from my patient or patient’s family how they want to be involved in making the nursing care decision” ( ) are the main key factors for the beginning of nursing decision. In the discussion and decision stages, the corresponding key factors are “I made it clear to my patient or patient’s family that a nursing care decision needs to be made” ( ) and “I asked my patient or patient’s family which nursing care option they prefer” ( ). The result’s statistical significance confidence and gap error were 98.106% and 1.894%, respectively. Conclusions. When making nursing decisions with patients, orthopedic nurses need to have detailed information about how patients are involved in SDM and all relevant information. Nurses should also inform patients and their families regarding the purpose of the discussion, namely, to help one understand the content, advantages, and disadvantages of the nursing care options, and finally, make a decision.